Modeling of Electromagnetic Fields in Parallel-Plane Structures: A Unified Contour-Integral Approach - Stumpf, Martin (Společnost pro radioelektronické inženýrství, 2017)
A unified reciprocity-based modeling approach for analyzing electromagnetic fields in dispersive parallel-plane structures of arbitrary shape is described. It is shown that the use of the reciprocity theorem of the time-convolution type leads to a global contour-integral interaction quantity from which novel both time- and frequency-domain numerical schemes can be arrived at. Applications of the numerical method concerning the time-domain radiated interference and susceptibility of parallel-plane structures are discussed and illustrated on numerical examples.
Keywords: Contour integral method; integral equations; electromagnetic compatibility; electromagnetic interference; reciprocity theorem; numerical analysis